Temporal Distribution of Bird Species in the Sarinah Island Porong Sidoarjo - Vendy Adrinanda; Nia Kurniawan (Biotropika: Journal of Tropical Biology, 2013)
Temporal Distribution of Bird Species in the Sarinah Island Porong Sidoarjo Vendy Adrinanda, Nia Kurniawan Department of Biology, Faculty of Mathematics And Natural Sciences Brawijaya University Birds are members of the vertebrate animals that have feathers and wings. It has given many useful in the human life, as such as many birds species and population in the nature can be used for tourist area. This study aims to determine the temporal distribution and bird species in the Sarinah island. This research use point count combination methode. Observation is done by explored island’s area which will be used as research’s location, and then devide the area with GPS become 4 location point (1,2,3,4). Observation is done 3 times: first, in the morning at 6.00-7.00 o’clock; second, in the afternoon at 12.00-13.00 o’clock; and third, in the evening at 15.30-16.30; during four days that’s two days between 10th-15th Javanese month and two days between 25th-30th Javanese month. Birds species which be found in every location point must be identified and administrated as field data. The identified methode is by taken the birds photoes for every species, count their number and administrate this data into observation data, birds species idetified by literature examination. Spreading map bird species and location that has found to tabulated into microsoft excel and then it is managed in Quantum GIS. Result of the research shows that has been found 44 bird species and divide 24 families. Species that often be found with many individual amount is walet linchi (Collocalia linchii). The bird species often be found in a great number beside 10-15 Javanese month more than beside 25-30 Javanese month, because beside 10-15 javanese month is tides occur and beach to be receding. And according their spreading status, can be devided into 33 species domestic and 11 species migrant. Keywords: birds, temporal distribution, family, species, distribution status.